Justiça, comprometimento, consentimento e comportamento de cidadania organizacional: um estudo com jovens trabalhadores - Samara de Menezes Lara (2024)
This thesis aims to analyze how perceptions of organizational justice, bonds of affective commitment and organizational consent and organizational citizenship behaviors are related, in the perception of young workers. To enable this research, young workers inserted into organizations through the quota established by the Apprenticeship Law were chosen as the target audience. Studies with this audience are relevant due to their intricate involvement, in specific and often adverse ways, in the instabilities of the labor market. For this purpose, a quantitative, descriptive study was conducted, with data collected through an electronic questionnaire consisting of sociodemographic questions and previously validated scales of distributive and procedural justice (Gomide Jr; Siqueira, 2008) and interactional justice (Rego et al., 2002), commitment (Bastos; Aguiar, 2015), consent (Silva; Bastos, 2015), and organizational citizenship behaviors (Bastos; Siqueira; Gomes, 2014). Data were analyzed using three techniques: confirmatory factor analysis (CFA), univariate descriptive analysis, and structural equation modeling (SEM). The sample (n=1,044) presented the following predominant characteristics: female, aged between 18 and 21 years old, working in the states of Minas Gerais and São Paulo, with a tenure between 6 months and 1 year in the company, and a family income of 1 to 2 minimum wages. CFA demonstrated the applicability of the scales to the surveyed population, with only 01 item from the procedural justice scale and 01 item from the consent scale being removed. Finally, causal relationships were tested using SEM, in which out of the 21 hypotheses tested, 13 were validated. The results denote that the tested model was partially supported, with all hypotheses that considered the dimensions of justice as an antecedent of affective commitment and organizational signature supported, all hypotheses that considered affective commitment as an antecedent being supported, all hypotheses that considered the Cooperation with colleagues as a supported consequence, in this item it is highlighted that the hypothesis that distributive justice impacts cooperation with colleagues exhibited a negative relationship (path coefficients), revealing an inverse relationship between these constructs. This study contributes to theory by developing theoretical models and validating them through empirical research, enabling the verification of the validity of literature assumptions, either confirming their applicability in a specific work context, such as that of young workers, and identifying nuances that may challenge them. In practical terms, the feedback from the results of this research to the Professional Education Institution (IEP) will enable the development of strategies, policies, and practices to improve aspects considered unfair by young people, promoting dialogue and possibilities for fairer and more equitable work environments. Lastly, in terms of social contribution, this analysis sheds light on the working conditions of this group of workers, providing information that can assist in the formulation and/or reformulation of public policies directed towards them. Given the limitations of the study, a research agenda has been outlined, emphasizing the importance of additional investigations involving other participants of different age groups and hierarchical positions, as well as qualitative research.